CO2/Basalt's interfacial tension and wettability directly from gas density: Implications for Carbon Geo-sequestration - Abdulelah, H. (Elsevier B.V., 2021)
There is an urgent need to store millions of tons of CO2 in deep underground formations to reduce anthropogenic emissions in the atmosphere. Basaltic rocks are recently depicted as feasible and safe candidates for storing CO2 in mineralized form. The leakage of stored CO2 in basaltic rocks could be minimized due to the mineralization process reported to occur in timescales magnitude shorter than those predicted for sandstone reservoirs. Rock/CO2 interfacial tension and wettability are essential factors to understand the interaction between CO2 and basalt rocks. Low values of rock/CO2 interfacial tension suggest stronger CO2-rock interaction, thus lower CO2 capacity is inferred, and vice versa. In other words, low values of rock/CO2 interfacial tension indicate stronger adhesion of CO2 molecules onto the rock surface. In this study, we have experimentally investigated basalt/CO2 interfacial tension under various pressures ranged from 4 MPa to 20 MPa and at temperatures of 308o K and 333o K. Our findings suggest that, as expected, Basalt/CO2 interfacial tension decreases as the pressure increases and increases as the temperature increases; solid/water interfacial energy decreases with increasing the temperature. The results also revealed that Basalt's CO2 sealing capacity is reduced as the contact angle (pressure) and temperature increases. The CO2 sealing capacity was reduced by up to 50 as the contact angle became ~80Â° or when the pressure reached 17 MPa. We also found that there is a remarkable relationship between Basalt/CO2 IFT and CO2 density (Ï) at 308 K and 333 K. The introduced relationship could serve as a handy tool to give a quick prediction of IFT CO2/basalt in basaltic formation or other CO2/solid systems. Determining solid/gas surface energy helps explain why minerals/rocks offer different wettability at certain pressure and temperature, leading to a better understanding of geological CO2-storage processes. Â© 2021 Elsevier B.V.